Compositional optimization of mixed cation Dion–Jacobson perovskites for efficient green light emission. Issue 1 (24th November 2021) - Qin, Xinshun; Liu, Fangzhou; Leung, Tik Lun; Sun, Wenting; Chan, Christopher C. S.; Wong, Kam Sing; Kanižaj, Lidija; Popović, Jasminka; Djurišić, Aleksandra B.
Abstract : The use of mixed spacer cations in quasi-2D Dion–Jacobson perovskites results in changes in film phase composition and efficient funneling for optimal composition. Optimal composition devices achieve a maximum EQE of 12.85% with TPPO passivation. Abstract : Dion–Jacobson (DJ) perovskites have been demonstrated to be highly promising for improved lifetime and stability of solar cells, but their applications in light emitting diodes (LEDs) have been scarce. A large number of potential spacer ligands have not been explored, offering potential to achieve significant improvements in spectral regions where DJ perovskite-based LEDs lag behind other perovskite counterparts. Therefore, we investigated the effect of the choice of spacer cation on the properties and green light emitting diode applications of DJ perovskites. We found that optimized mixing of the spacer cations results in perovskite films with improved morphology and a change in phase distribution, leading to enhanced funneling and more efficient light emission. Devices containing mixed spacer cations 1, 6-hexanediammonium (HDA) and 1, 10-decanediammonium (DDA) exhibited significant enhancement of the external quantum efficiency (EQE), with a maximum value for DDA0.75 HDA0.25 of 9.41% significantly higher than that obtained for pure HDA (1.23%) and DDA (7.28%), as well as increased lifetime with T 50 of 70 min for the optimized composition, compared to 4 min for pure HDA and 60 min for pure DDA. The maximum EQE can be further increased by triphenylphosphine oxide passivation to 12.85%.